Two new synonymies in the genus Praocis (Coleoptera: Tenebrionidae) - Flores, Gustavo Ernesto (2010)
The genus Praocis Eschscholtz, 1829 belongs to Praocini, an endemic Neotropical tribe of Pimeliinae from southern South America. According to the last revision (Kulzer 1958) Praocis comprises 77 species and 7 subspecies arranged in ten subgenera, distributed from central Peru to the southern part of Patagonia in Argentina and Chile.